2006
DOI: 10.1016/j.bbr.2005.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Selective increase of dark phase water intake in neuropeptide-Y Y2 and Y4 receptor knockout mice

Abstract: Neuropeptide-Y (NPY) is involved in the regulation of ingestive behaviour and energy homeostasis. Since deletion of the NPY Y2 and Y4 receptor gene increases and decreases food intake, respectively, we examined whether water intake during the light and dark phase is altered in Y2 and Y4 receptor knockout mice. The water consumption of mice staying in their home cages was measured by weighing the water bottles at the beginning and end of the light phase during 4 consecutive days. Control, Y2 and Y4 receptor kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(60 reference statements)
2
5
1
Order By: Relevance
“…However, other endogenous mediators such as endothelin-1 or neuropeptide Y have also been found to correct the in vitro mesenteric vascular hyporesponsiveness in portal hypertension [10] and might hence likewise be involved in the beneficial effect of water restriction [34] . In agreement with this notion, neuropeptide Y is reportedly involved in the regulation of water intake and thirst [35] , and [36] dehydration stimulates the endogenous release of endothelin-1 [37] .…”
Section: Discussionsupporting
confidence: 61%
“…However, other endogenous mediators such as endothelin-1 or neuropeptide Y have also been found to correct the in vitro mesenteric vascular hyporesponsiveness in portal hypertension [10] and might hence likewise be involved in the beneficial effect of water restriction [34] . In agreement with this notion, neuropeptide Y is reportedly involved in the regulation of water intake and thirst [35] , and [36] dehydration stimulates the endogenous release of endothelin-1 [37] .…”
Section: Discussionsupporting
confidence: 61%
“…The proabsorptive effect is obviously carried via Y2 receptors, and is of medical interest in malabsorptive conditions (short bowel syndrome), and in diseases (enterocolitis, cholera, Krohn's disease). Also, deletion of either the Y2 or the Y4 receptor in the mouse was shown to increase the dark‐phase water intake ( Wultsch et al , 2006 ), indicating a decrease in water absorption due to the receptor knockouts. It should be noted that the antisecretory effects of PYY could involve the Y4 and Y1 receptors in addition to the Y2 receptor ( Souli et al , 1997 ).…”
Section: The Y2 Receptor In Behavior and Diseasementioning
confidence: 99%
“…In addition GR231118, a homodimeric peptide based on the C-terminal sequence of NPY [(Ile, Glu,Pro,Dpr,Tyr,Arg,Leu,Arg,Try-NH 2 )-2-cyclic(2,4Ј),(2Ј,4)-diamide, also known as 1229U91] was originally identified as a competitive Y 1 receptor antagonist with low Y 2 affinity (Daniels et al, 1995;Hegde et al, 1995), but this dimeric nonapeptide also has Y 4 affinity and efficacy (Matthews et al, 1997;Parker et al, 1998;Schober et al, 1998Schober et al, , 2000. The recent generation of Y 4 knockout ( Ϫ/Ϫ ) mice provides the only current alternative to explore the loss of specific function associated with obesity (Sainsbury et al, 2002), cardiac function (Smith-White et al, 2002), and water intake (Wultsch et al, 2006). These studies found that Y 4 Ϫ/Ϫ mice are leaner, have decreased resting heart rate with lower arterial blood pressure, and increased dark phase water intake compared with wild-type (WT) mice.…”
mentioning
confidence: 99%